CLINICAL FEATURES OF CROHN'S DISEASE AND ULCERATIVE COLITIS - MALIK, Z; SHAHID, HA; MALIK, M (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in the Department of Gastroenterology, THQ Hospital, from March 2020 to March 2021 to assess CD and UC's clinical characteristics and demographic features in a relatively diverse group of patients. The study included patients diagnosed with IBD. The questionnaire was used to gather data regarding clinical and demographic features, disease duration, and family history of IBD, surgical interventions, extra-intestinal manifestations, and clinical and socio-economic variables relevant to CD and UC patients. 500 patients were included in the study, of which 135 (28%) had CD and 365 (73%) had UC. UC patients predominantly had bloody diarrhea and/or hematochezia, while CD patients had abdominal pain. 50% of CD patients required surgical intervention, compared to only 9.8% of UC patients. Evaluation of chemotherapy showed that 66.6% of CD patients and 37.8% of UC patients received steroid therapy. 22 (6%) UC patients and 7 (5.1%) CD patients had a family history of IBD (P=.819). The most frequent extra-intestinal complication in UC patients was PSC; it was acute arthropathy in CD patients. It is concluded that the peak age of disease onset in UC and CD patients is similar to other Asian countries. There was non-significant male predominance for UC and CD. Diagnosis of CD is delayed compared to UC, which may be due to negligence towards disease symptoms.